Answer:
ax = 1.23 m/s²
ay = -6.32 m/s²
Step-by-step explanation:
The acceleration is equal to the change in velocity over time. So, the acceleration of in the x-component is equal to
![a_x=(v_(fx)-v_(ix))/(t)](https://img.qammunity.org/2023/formulas/physics/college/5iaf8ldd0b8abt8v5oxn7i4m0h8irdxw2m.png)
Where vfx is the final velocity on the x-direction which is equal to 0 m/s because at the end the velocity is in the y-axis. vix is the initial velocity which is -2.70 m/s and t is the time, so t = 2.20s.
Replacing the values, we get:
![a_x=\frac{0-(-2.70\text{ m/s\rparen}}{2.20\text{ s}}=1.23\text{ m/s}^2](https://img.qammunity.org/2023/formulas/physics/college/x6u9ik6lv0avf011iwzxl0sajsjtvxfb65.png)
In the same way, we can calculate the y-component of the acceleration as
![a_y=(v_(fy)-v_(iy))/(t)](https://img.qammunity.org/2023/formulas/physics/college/zp4jbe690l9yyu6i6i7j04y1mkmxtjiri9.png)
Replacing vfy = -13.9 m/s and viy = 0 m/s, we get:
![a_y=\frac{-13.9\text{ m/s - 0 m/s}}{2.20\text{ s}}=-6.32\text{ m/s}^2](https://img.qammunity.org/2023/formulas/physics/college/85up20br9c14g1gedc4o89s1x6fr9blcbt.png)
Therefore, the answer is
ax = 1.23 m/s²
ay = -6.32 m/s²